What Are We Doing When We Are Doing Epistemology? - Ram Neta (Baltic International Yearbook of Cognition, Logic and Communication, 2026)
Jody Azzouni’s (2025b) paper “Use and mention with respect to ‘know’, ‘believe’, ‘evidence’, ‘justification’, ‘hypothesis’, and so on: A hot mess” makes a number of important and valuable points. In this paper, I try to show that Azzouni’s philosophical procedure can survive the worries that he considers, and unsatisfactorily addresses, in Section 16 of his paper.